Daya Antagonis Jamur Trichoderma sp. Terhadap Jamur Diplodia sp. Penyebab Busuk Batang Jeruk Siam (Citrus nobilis) - Riza Linda, Aan Sundari, Siti Khotimah, (Universitas Tanjungpura, 2014)
Stem and branch parts of citrus trees is often attacked by blendok disease caused by the fungus Diplodia sp. Control of the disease by using synthetic fungicides are less effective in controlling diseases caused by fungal pathogens. Fungal biological control is using Trichoderma sp. as an antagonist agents. This study aimed to determine the antagonists power of fungus Trichoderma sp. in controlling fungus Diplodia sp. causes of citrus stem rot. Antagonist test covers the wide average of mycelium and calculate the percentage of antagonistic fungus Trichoderma sp. from day 1st to 7th. Results showed that the fungus Trichoderma sp. can inhibit the growth of fungus Diplodia sp. with an area of?? mycelium on day 6 and day 7 of 6240 mm2 with antagonists percentage reaches 100%.